PELATIHAN INTERNET BANKING DAN MOBILE BANKING BAGI GURU PEMASARAN SERTA PELAKU UKM DI WILAYAH SURABAYA - Devica, Sadana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Internet banking and mobile banking training for marketing teachers and small and medium enterpries (SMEs) in the Surabaya region is one form of community service activities carried out by the Ubaya Polytechnic Marketing Management Study Program. This activity is carried out with the aim to provide participants with insights on how to use internet banking and mobile banking. This training was held on July 6, 2019 at Ubaya Polytechnic Campus Surabaya, which was attended by 38 participants. The method used in this training is to socialize how to use internet banking or mobile banking as a payment transaction tool that is often used today. The results achieved from this training activity are that participants can utilize existing technology, especially in the banking sector more effectively.